2011
DOI: 10.1016/j.jadohealth.2010.12.017
|View full text |Cite
|
Sign up to set email alerts
|

Risk and Protective Factors for Adolescent Substance Use in Washington State, the United States and Victoria, Australia: A Longitudinal Study

Abstract: Purpose Compare the levels of risk and protective factors and the predictive influence of these factors on alcohol, tobacco and cannabis use over a 12-month follow-up period in Washington State in the United States and Victoria, Australia. Method Longitudinal school-based survey of students drawn as a 2-stage cluster sample recruited through schools, and administered in 2002 and 2003 in both states. The study uses state-wide representative samples of students in Grades 7 and 9 (N = 3876) in Washington State … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
151
3
16

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 134 publications
(187 citation statements)
references
References 23 publications
17
151
3
16
Order By: Relevance
“…A survey conducted in United States of America indicated that the average age of initiation to alcohol use among young people is 15 years [5]. Another survey conducted in Thai indicated that 79.7% of Thai current drinkers are over 15 years old and was reported that the youth initiate to alcohol drinking between the ages of 15-24 years [6]. In Ghana, a study conducted among second cycle and out of school youth on substance use revealed that average age for first use of substance was between [14][15][16][17][18][19] years and the highest use was between the ages of 16-23 years.…”
Section: Introductionmentioning
confidence: 99%
“…A survey conducted in United States of America indicated that the average age of initiation to alcohol use among young people is 15 years [5]. Another survey conducted in Thai indicated that 79.7% of Thai current drinkers are over 15 years old and was reported that the youth initiate to alcohol drinking between the ages of 15-24 years [6]. In Ghana, a study conducted among second cycle and out of school youth on substance use revealed that average age for first use of substance was between [14][15][16][17][18][19] years and the highest use was between the ages of 16-23 years.…”
Section: Introductionmentioning
confidence: 99%
“…These four comic-style animated tales introduce common risk factors of adolescent psychoactive substance use (e.g. peer pressure, peer recognition for substance use involvement, social isolation, a dysfunctional family background indicated by symptoms like familial substance use and either sexual, physical or emotional victimization) based on the findings of former studies [33,34], as well as potential way-outs by presenting four types of treatments: a) art therapy, b) individual psychotherapy, c) group therapy including self-support groups, d) animal-assisted therapy. The interactivity of this module means that the dialogues are triggered by the user, and turns are indicated by slight movement of the main characters'.…”
Section: Detailed Characteristics and Aims Of The Modules Animated Comentioning
confidence: 99%
“…La etiología del consumo de cánnabis -esporádico o problemático-en población adolescente es multicausal (Hemphill et al, 2011), interactuando factores de riesgo individuales (Magallón-Neri et al, 2012;Szerman, Goti, Díaz, y Arango, 2014;ter Bogt et al, 2014), familiares (Becoña, Fernández del Río, Calafat, y Fernández-Hermida, 2014;Brière, Fallu, Descheneaux, y Janosz, 2011;Creemers et al, 2015), escolares (Guxens, Nebot, Ariza, y Ochoa, 2007;Hall y Degenhardt, 2009) y ambientales (Observatorio Europeo de las Drogas y las Toxicomanias, 2014;Peña-fiel, 2009;Szerman et al, 2014).…”
unclassified